1989
DOI: 10.1099/00221287-135-9-2413
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Intracellular Acidification Induced by Glucose in Saccharomyces cerevisiae

Abstract: Addition of glucose or fructose to cells of Saccharomyces cerevisiae adapted to grow in the absence of glucose induced an acidification of the intracellular medium. This acidification appeared to be due to the phosphorylation of the sugar since : (i) glucose analogues which are not efficiently phosphorylated did not induce internal acidification; (ii) glucose addition did not cause internal acidification in a mutant deficient in all the three sugar-phosphorylating enzymes; (iii) fructose did not affect the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Cells grown in selective medium to retain the pHluorin plasmid were deprived of glucose for ϳ30 min and then monitored before and after the addition of glucose to 50 mM final concentration. As shown by others using pHluorinbased and other methods (22,23), Fig. 2A illustrates that the addition of glucose to glucose-deprived wild-type cells results in a transient cytosolic acidification within a minute of glucose addition followed by a rapid rise in cytosolic pH that is complete within 3 min of glucose addition.…”
Section: Vph1-containing V-atpase Complexes Are Essential For Vacuolamentioning
confidence: 98%
“…Cells grown in selective medium to retain the pHluorin plasmid were deprived of glucose for ϳ30 min and then monitored before and after the addition of glucose to 50 mM final concentration. As shown by others using pHluorinbased and other methods (22,23), Fig. 2A illustrates that the addition of glucose to glucose-deprived wild-type cells results in a transient cytosolic acidification within a minute of glucose addition followed by a rapid rise in cytosolic pH that is complete within 3 min of glucose addition.…”
Section: Vph1-containing V-atpase Complexes Are Essential For Vacuolamentioning
confidence: 98%
“…The regulation of Pma1 ATPase by glucose at the molecular level is not yet fully understood, but the maintenance of proper internal pH is essential for enzyme activity and allows the cell to survive at a low environmental pH (33,41). Acidification of the external medium is a complex process involving many cellular components.…”
Section: Figmentioning
confidence: 99%
“…Studies with S. cerevisiae have shown that, in response to that acidification, the plasma membrane H + -ATPase pumps protons out of the cell in a ATPdependent mechanism (Eraso and Gancedo 1987;Ramos et al 1989). Similar mechanisms in S. cerevisiae has been observed with sorbic acid, which induces a stimulation of the plasma membrane H + -ATPase activity and a drastic reduction of cellular ATP level (Holyoak et al 1996).…”
Section: Introductionmentioning
confidence: 86%